The Formulation of Production Strategy and Competitive Priorities of Production - Konda, Iva (Naše gospodarstvo/Our economy, 2012)
The formulation of production strategy includes a discussion about the production strategy, factors of influence or decision-making areas in the production function, and its connection with competitive priorities of production. The production strategy should correspond to and comply with the strategy of an organisation as a whole as well as other specific strategies, particularly marketing. The production strategy is included in the strategic plan of a company as its integral component and a starting point for the formulation of business strategy. Each company should be aware of the importance of the production strategy in order to achieve competitive advantages. The paper shows the production strategy in the selected company.